Allergic Contact Dermatitis Among Healthcare Workers Exposed to Glutaraldehyde - Rita I Wijaya; Muhammad Ilyas (The Indonesian Journal of Community and Occupational Medicine, 2021)
Background: One of the health problems that can be caused by glutaralaldehyde is allergic contact dermatitis (ACD). However, the causal relationship between glutaraldehyde and DKA is still unclear, so it is necessary to look for some evidence regarding this relationship. The search for evidence is also equipped with a seven-step assessment of occupational diseases therefore it can assist occupational medicine doctors who find patients with ACD and have a history of exposure to glutaraldehyde. Methods: Literature search using Pubmed, Scopus and JSTOR databases. The keywords used are ‘healthcare worker OR healthcare personnel’, ‘glutaraldehyde’ and ‘allergic contact dermatitis. Article selection was performed using the defined inclusion and exclusion criteria. Selected articles will be critically reviewed based on etiological studies from the Oxford Center of Evidence-Based Medicine. Result: It was in six selected articles that met the inclusion and exclusion criteria. The main finding after a critical review was that glutaraldehyde may increase the risk of ACD. Conclusion: There is a relationship between 1% glutaraldehyde exposure and the incidence of ACD in health workers. To establish the diagnosis of occupational diseases in health workers who are exposed to glutaraldehyde, seven steps of diagnosis of occupational diseases are used.